2018
DOI: 10.1016/j.memsci.2018.04.040
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced gas separation performance of 6FDA-DAM based mixed matrix membranes by incorporating MOF UiO-66 and its derivatives

Abstract: Functionalization and post-synthetic modification (PSM) of metal-organic frameworks (MOFs) are two important routes to obtain MOFs with full potential in mixed matrix membrane (MMM) fabrication. We synthesized UiO-66 and two derivatives UiO-66-NH 2 and UiO-66-NH-COCH 3 with less than 50 nm particle size. The CO 2 uptakes at 10 bar in the two functionalized UiO-66s were improved by 44% and 58%, respectively, with respect to the pristine solid. The MOF nanoparticles were incorporated into the highly permeable po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
101
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 144 publications
(106 citation statements)
references
References 109 publications
(164 reference statements)
1
101
1
Order By: Relevance
“…In fact, literatures show that mixed gas permeation could yield relatively better performance than pure gas permeation at low feeding pressures . Experimental results were summarized in Figure , compared with literatures7c,12c,d,13,14,15b,16,25 (Tables S4–S6). As illustrated in Figure a–d, the introduction of MOFs increases the gas permeabilities (CO 2 and H 2 ) noticeably and an intrinsic selectivity is attained at a loading as high as 55 wt%.…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations
“…In fact, literatures show that mixed gas permeation could yield relatively better performance than pure gas permeation at low feeding pressures . Experimental results were summarized in Figure , compared with literatures7c,12c,d,13,14,15b,16,25 (Tables S4–S6). As illustrated in Figure a–d, the introduction of MOFs increases the gas permeabilities (CO 2 and H 2 ) noticeably and an intrinsic selectivity is attained at a loading as high as 55 wt%.…”
Section: Resultsmentioning
confidence: 97%
“…More significantly, despite this potential, only a handful of MOF‐based hybrid membranes have performed at or beyond current Robeson upper bounds. Furthermore, the few successful cases, like CO 2 /CH 4 ,12c predominantly rely upon rigid PIMs7c,14a,15 or an aggressive thermal annealing process, adding complications which hinder practical applicability 14a. In addition, most hybrid membranes reported are limited in scope and highly optimized for a particular gas pair (e.g., CO 2 /CH 4 , C 2 , or C 3 ), thus lacking a more general approach to accommodate multicomponent gas mixture separations.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Molecular simulations demonstrated that CO 2 molecules generally tend to accumulate in the micro-voids at the MOF/polymer interface. Coronas's group [111] also combined experiments and molecular simulations to examine a 6FDA-DAM-based MMM with a different MOF filler, UiO-66, and reported enhanced gas separation performance of the MMM. Zhao et al [112] incorporated MOF nanosheets, NUS-8, into PIM-1 to prepare MMMs.…”
Section: The Role Of Computational Studies In Analyzing the Barriers mentioning
confidence: 99%